The Effect of Fuel Pump Pressure and Number of Injector Holes on 150cc Matic Motorcycle Performance - Santoso, Santoso; Yulianto, Fian Arif; Yudiyanto, Eko; Aditya, Candra; Sabarudin, Suriansyah (Asian Journal Science and Engineering, 2023)
This study aims to evaluate the effects of increasing fuel pump pressure and varying the number of holes in the injector on engine performance. The fuel system in the engine has evolved from carburettor to injection system to improve the efficiency of fuel usage. In this study, the fuel pump pressure was increased to three levels, namely 2.5 bar, 3 bar, and 3.5 bar. In addition, variations in the number of holes in the injector were also tested using 3-hole, 6-hole, and 8-hole injectors. Engine performance was evaluated based on the power and torque produced. The research method used is experimental with power and torque measurements as engine performance data. The results showed that increasing fuel pump pressure and varying the number of holes in the injector had a significant effect on engine performance. Increasing the fuel pump pressure to 3.5 bar results in an increase in engine power and torque. The best power test results were obtained at a fuel pump pressure of 3 bar with a combination of 6-hole injectors, producing a maximum power of 11.63 HP at 6000 rpm engine speed. While the best torque test results were obtained at a fuel pump pressure of 3.5 bar with a combination of 3-hole injectors, producing a maximum torque of 43.10 Nm at 3000 rpm. The variation in the number of holes in the injector shows that the use of injectors with more holes tends to increase engine power and torque. Keywords: Engine Performance, Fuel Pump Pressure, Fuel Efficiency Injector Holes, Injection System